Possibilities of Applying New Navigation Techniques in Military Equipment Testing - Maciej DORCZUK (Możliwości zastosowania nowych technik nawigacji w badaniach sprzętu wojskowego, 2019)
The article proposes the possibilities of testing military equipment using satellite navigation systems, as well as systems that aid such systems, used for determining the position of and indicating targets. The research employed modern civilian navigation devices using satellite navigation systems, as well as navigation aided by land-based reference stations. Using Trimble R8 and RT4000 devices in research is proposed. The possibilities of the RT4000 precise movement parameter measuring device within the scope of position determining using a portable reference station using the Trimble R4 receiver and Satel-TA18 radio (not the device’s standard equipment) are presented.
Keywords: Badania sprzetu wojskowego